Enhanced photoelectrochemical performances in photocatalytic pollutant degradation and water splitting by direct Z-scheme Bi2Sn2O7/TiO2 NTAs. Issue 3 (1st February 2022) - Hou, Junwei; Kong, Lingcong; Xie, Yu; Ma, Jingui; Liu, Yansheng; Chen, Mengmeng; Wang, Qingyao
Abstract: The construction of ternary metal oxide to improve photoelectrochemical performances of TiO2 photocatalysts is the hot topic in environmental and resource applications. Herein, Bi2 Sn2 O7 nanoparticles were deposited on TiO2 nanotube arrays (TiO2 NTAs) by the solvothermal technology only by changing reagent concentration. The solar absorption region of TiO2 NTAs was obviously extended into visible light after Bi2 Sn2 O7 sensitization, and the photoelectric performance was also significantly improved. The high visible light photocurrent density and photovoltage achieved 30.24 μA/cm 2 and -0.19 V, and the interface resistance was reduced that benefited the rapid electron transportation. The photocatalytic performances of methyl orange (MO), rhodamine b (RhB), methylene blue (MB) and Cr (VI) removal were enhanced, and 63.76%, 77.34%, 100% and 100% of these pollutants were photoremoved under solar irradiation. Moreover, the construction of direct Z-scheme Bi2 Sn2 O7 /TiO2 NTAs heterojunction was beneficial to the photoelectron transfer and active radical formation, and the experimental results indicated that OH and O2 - were the decisive species for the dye degradation. The samples also exhibited outstanding photocatalytic water splitting for H2 evolution, and the high efficiency (306.36 μmol·cm −2 ·h −1 ) and stability were confirmed. The excellent photocatalytic performances of the Bi2 Sn2 O7 /TiO2 NTAs photoelectrodes showed extensive potential applications in environmental pollution and green resource exploitation.